2013
DOI: 10.1021/pr4008305
|View full text |Cite
|
Sign up to set email alerts
|

N-Glycan Abnormalities in Children with Galactosemia

Abstract: Galactose intoxication and over-restriction in galactosemia may affect glycosylation pathways and cause multisystem effects. In this study, we describe an applied hydrophilic interaction chromatography ultra-performance liquid chromatography high-throughput method to analyze whole serum and extracted IgG N-glycans with measurement of agalactosylated (G0), monogalactosylated (G1), and digalactosylated (G2) structures as a quantitative measure of galactose incorporation. This was applied to nine children with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 57 publications
2
59
1
Order By: Relevance
“…It is not clear if ongoing glycosylation abnormalities further modify the observed outcomes. 21,28 In our previous studies of circulating IgG N-glycans, we demonstrated correction of the gross assembly defects in young galactosaemia patients following treatment with galactose restriction. 28 We also demonstrated the presence of IgG N-glycan processing defects in adults and children with galactosaemia maintained on a galactose restricted diet using IgG galactose incorporation ratios.…”
Section: Introductionmentioning
confidence: 87%
“…It is not clear if ongoing glycosylation abnormalities further modify the observed outcomes. 21,28 In our previous studies of circulating IgG N-glycans, we demonstrated correction of the gross assembly defects in young galactosaemia patients following treatment with galactose restriction. 28 We also demonstrated the presence of IgG N-glycan processing defects in adults and children with galactosaemia maintained on a galactose restricted diet using IgG galactose incorporation ratios.…”
Section: Introductionmentioning
confidence: 87%
“…Serum was prepared from freshly spun blood samples and immediately frozen at −20 °C. IgG isolation was performed on a robotized glycomics platform as described previously, using Protein G 96-well filter plates (Fisher Scientific, Pittsburgh, PA) (7,37). The purity of the isolated IgG was assessed using 10 % reducing SDS-PAGE in an Xcell SureLock Mini-Cell (Invitrogen, Carlsbad, CA) according to the manufacturer's instructions (data not shown).…”
Section: Soluble Leptin Receptor (Sob-r)mentioning
confidence: 99%
“…N-glycans were released from IgG using the automated method and peptide N-glycanase F (1,000 U/ml) as described elsewhere (7,22). Released N-glycans were then labeled by reductive amination with the fluorophore 2-AB 41,42 using a Ludger Tag 2-AB glycan labeling kit as described by the manufacturer (Ludger, Oxford, UK).…”
Section: Soluble Leptin Receptor (Sob-r)mentioning
confidence: 99%
See 2 more Smart Citations